2016
DOI: 10.3390/ma9010043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Post-Plasma Treatment Storage Conditions on the Shear Bond Strength of Veneering Porcelain to Zirconia

Abstract: This in vitro study investigated whether different storage conditions of plasma-treated zirconia specimens affect the shear bond strength of veneering porcelain. Zirconia plates were treated with a non-thermal atmospheric argon plasma (200 W, 600 s). Porcelain veneering (2.38 mm in diameter) was performed immediately (P-I) or after 24 h storage in water (P-W) or air (P-A) on the treated surfaces (n = 10). Untreated plates were used as the control. Each group was further divided into two subgroups according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 29 publications
5
43
1
Order By: Relevance
“…According to some XPS (X-ray Photoelectron Spectroscopy) study, APP-treated ceramic surface showed that the content of C-C bonds decreased, suggesting that organic matter was removed. By contrast, the content of oxygen-containing polar groups increased (C-O-C and O=C-O), suggesting that APP treatment enhanced the surface hydrophilicity [32,35,36].…”
Section: Discussionmentioning
confidence: 95%
“…According to some XPS (X-ray Photoelectron Spectroscopy) study, APP-treated ceramic surface showed that the content of C-C bonds decreased, suggesting that organic matter was removed. By contrast, the content of oxygen-containing polar groups increased (C-O-C and O=C-O), suggesting that APP treatment enhanced the surface hydrophilicity [32,35,36].…”
Section: Discussionmentioning
confidence: 95%
“…In relation to the veneering ceramic, the following commercial brands were used: IPS e.max Ceram, Cercon Ceram, Vita VM9, Cerabien ZR, and Vintage ZR . Three studies did not specify the veneering ceramic used for the zirconia veneer.…”
Section: Resultsmentioning
confidence: 99%
“…In relation to the method of specimen manufacturing, some studies did not clarify the method used. Among those that did, five studies manufactured specimens through CAD/CAM systems, one study used manual methods, with the help of carborundum discs, while others manufactured their specimens with high‐precision machines (ISOMET, MicroSlice).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations